The indentification, contiguous sequence annotation, cloning and site-directed mutagenesis of the P100 vaccine candidate gene of the ostrich mycoplasma Ms02 - Steenmans, Shandre (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MSc (Biochemistry))--University of Stellenbosch, 2010.